Crotoliganfuran, a new clerodane-type furano-diterpenoid from Croton oligandrus Pierre ex Hutch. Issue 1 (2nd January 2021) - Yannick Stephane, Fongang Fotsing; Dawe, Amadou; Angelbert Fusi, Awantu; Jean Jules, Bankeu Kezetas; Ulrich, Kagho Kenou Donald; Lateef, Mehreen; Bruno, Lenta Ndjakou; Ali, Muhammad Shaiq; Ngouela, Silvère Augustin
Abstract: The phytochemical investigation of the methanol extract of the bark of Croton oligandrus Pierre ex Hutch yielded a new clerodane-type diterpenoid crotoliganfuran (1 ) along with ten other compounds including 12-epicrotocorylifuran (2 ), lupeol (3 ), syringic acid (4 ), aleuritolic acid acetate (5 ), aleuritolic acid (6 ), scopoletin (7 ), geddic acid (8 ), β -sitosterol (9 ), vanilic acid (10 ) and stigmastane-3, 6-dione (11 ). Their structures were established by spectroscopic means. The extract and all the isolates were screened for their inhibitory properties against butyrylcholinesterase and urease enzymes, respectively. The extract and compounds 1, 4 and 7 displayed the most potent urease inhibitory properties with IC50 values, 22.2, 26.7 and 28.5 µ M, respectively. Compound 9 was the most active of all the tested compounds against butyrylcholinesterase enzyme with an IC50 value of 36.3 µ M.